Aerobic exercise training-induced irisin secretion is associated with the reduction of arterial stiffness via nitric oxide production in adults with obesity - Inoue, Kenichiro; Fujie, Shumpei; Hasegawa, Natsuki; Horii, Naoki; Uchida, Masataka; Iemitsu, Keiko; Sanada, Kiyoshi; Hamaoka, Takafumi; Iemitsu, Motoyuki (Applied physiology, nutrition, and metabolism, 2020)
This study aimed to clarify whether muscle-derived irisin secretion induced by aerobic exercise training is involved in reduction of arterial stiffness via arterial nitric oxide (NO) productivity in obesity. In animal study, 16 Otsuka Long-Evans Tokushima Fatty (OLETF) rats with obesity were randomly divided into 2 groups: sedentary control (OLETF-CON) and 8-week aerobic treadmill training (OLETF-EX) groups. In human study, 15 subjects with obesity completed 8-week aerobic exercise training for 45 min at 60%–70% peak oxygen uptake intensity for 3 days/week. As a result of animal study, carotid-femoral pulse wave velocity (cfPWV) was decreased, and arterial phosphorylation levels of AMP-activated protein kinase (AMPK), protein kinase B (Akt), and endothelial NO synthase (eNOS), circulating levels of nitrite/nitrate (NOx) and irisin, and muscle messenger RNA expression of fibronectin type III domain containing 5 (Fndc5) were increased in the OLETF-EX group compared with OLETF-CON group. In a human study, regular aerobic exercise reduced cfPWV and elevated circulating levels of NOx and irisin. Furthermore, change in circulating irisin levels by regular exercise was positively correlated with circulating NOx levels and was negatively correlated with cfPWV. Thus, aerobic exercise training-induced increase in irisin secretion may be related to reduction of arterial stiffness achieved by NO production via activated arterial AMPK–Akt–eNOS signaling pathway in obesity. Novelty Aerobic exercise training promoted irisin secretion with upregulation of muscle Fndc5 gene expression in rats with obesity. Irisin affected the activation of arterial AMPK–Akt–eNOS signaling by aerobic exercise training. Increased serum irisin level by aerobic exercise training was associated with reduction of arterial stiffness in obese adults.